Politik Santri Dalam Daur Ulang Kontrak Sosial - Abdul Munir Mulkhan (Universitas Islam Indonesia, 2004)
The following article tries to trace the reflection regarding santri political world at national stage. The groups of santri believe that they are as representatives of moslem communities although that fact shows that the groups of santri always failto get full supporting from moslem majority. Democracy places the voice of majority as the truth source that handled by the people. This principle of democracy can not be understood that contrary to the the doctrine system of Islam when moral quality of political party leaders, that of legislative, that of the candidate of president and that ot vice president.